Pendidikan Moral Emile Durkheim dan Relevansinya Terhadap Pendidikan - Peni Astuti; Sam’un Mukramin; Lukman Ismail; Yusdayanti Yusdayanti; Israwati Israwati; Yuyun Karlina (Journal on Education, 2023)
Morality is very important for human life. In the modern era like today, there have been various advances in all aspects of human life, but some of these advances have not been accompanied by progress in human morality. So it is known that most educational figures, especially two figures who offer ideas about moral education such as Al-Ghazali and Emile Durkheim. There are 3 foundations put forward by Durkheim to become a moral human being, namely discipline, group attachment, and autonomy. Everyone must have these three factors to become a moral individual. Moral education is a way of teaching someone to behave well so that they become good people and are accepted in social life. Through society, moral education can be grown in a person, especially in the growth and development of a child. Morality plays the most important role, because morality in all its forms can only exist in society. In addition, morality is not born from individuals but from society and is a symptom of society. The existence of moral discipline not only supports moral life itself, but has a wider impact. This moral discipline also plays an important role in the formation of character and personality in general